Fuzzy Quantification System untuk Menganalisis Pengaruh Minat Belajar dan Tingkat Kehadiran Mahasiswa terhadap Prestasi Belajar Mahasiswa Universitas Muhammadiyah Purwokerto - Ridho Muktiadi; Hindayati Mustafidah (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2012)
The one of measurement to know someone’s ability is the grades of a study. The grades result of a study can be influenced by some factors, there are interest in study and presence. The purpose of this research is to analyze the influence of student’s interest in study and level of presence toward their learning achievement of students of Muhammadiyah University of Purwokerto, by using Fuzzy Quantification Theory I to explain the qualitative grades that is interested in filling up the questionnaire in range of grade [0 1]. The result of this research show that there are any influence between sub indicator of interest in study, there is study hard toward is indicator with increase of the highest contribution toward student’s achievement, with their presence more than 10. The grades of increasing contribution to sub indicator of study hard is 1,6316 µ[x] toward category interest is 3,4152µ[x] that is influential toward student’s achievement of study (final grades)